1983
DOI: 10.7863/jum.1983.2.4.169
|View full text |Cite
|
Sign up to set email alerts
|

Unusual intrauterine objects: potential pitfalls in ultrasonographic identification.

Abstract: Three cases of echogenic objects in the uterine cavity are reported. These objects had ultrasonographic characteristics of contraceptive intrauterine devices (IUDs) and, in the absence of patients' medical histories, would almost certainly have been wrongly identified as such. The authors demonstrate that noncontraceptive intrauterine objects can mimic IUDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…While these health risks are well-researched with regard to food safety and regulation [ 201 ], it is concerning that many LAB are commonly used as probiotics. Indeed, another study has raised concern that some Lactobacillus rhamnosus strains often used in probiotics may produce biogenic amines [ 129 ].…”
Section: The Trace Aminergic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…While these health risks are well-researched with regard to food safety and regulation [ 201 ], it is concerning that many LAB are commonly used as probiotics. Indeed, another study has raised concern that some Lactobacillus rhamnosus strains often used in probiotics may produce biogenic amines [ 129 ].…”
Section: The Trace Aminergic Systemmentioning
confidence: 99%
“…In line with this, significant gender differences were reported for trace amine levels [ 126 ]. Furthermore—and specifically relevant to the review topic and IBS—trace amine synthesis has been reported in human neurons, where it is thought to modulate neuronal signalling [ 17 , 148 , 177 ], and high levels of trace amines have been found in specific foods, as well as bacterial secretomes [ 13 , 129 , 153 , 201 ]. Taken together, it is therefore possible that the trace aminergic system may be an additional level of control/maladaptation in IBS that has been largely overlooked until now.…”
Section: Introductionmentioning
confidence: 99%
“…In teressant ist aber, dass es auch ohne vorangehenden Abort oder Entzündung zu einer Endometriumossifikation kommen kann [8], Diagnostisch stehen verschiedene Mittel zur Verfü gung. Bereits im Ultraschall sind die Befunde recht ein drücklich, wenn auch nicht charakteristisch [9,10]. Ra diologisch sind Ossifikationen sichtbar, wenn zum Bei spiel anlässlich der Hysterosalpingographie eine Auf nahme vor Applikation des Kontrastmittels gemacht wird.…”
unclassified